2009
DOI: 10.1093/rheumatology/kep352
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity and disability in children with juvenile idiopathic arthritis one year following presentation to paediatric rheumatology. Results from the Childhood Arthritis Prospective Study

Abstract: Objective. Inflammatory arthritis in childhood is variable in terms of both presentation and outcome. This analysis describes disease activity in children with juvenile idiopathic arthritis (JIA) during the first year following presentation to a paediatric rheumatologist and identifies predictors of moderate to severe disability [defined using a Childhood HAQ (CHAQ) score ⩾0.75] at 1 year.Methods. The Childhood Arthritis Prospective Study recruits children <16 years with new inflammatory arthritis persisting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
59
7
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 13 publications
10
59
7
6
Order By: Relevance
“…The search of predictive factors of arthritis outcome has been the subject of many studies. Most of studies analyzed the outcome and poor prognosis in selected patients with already established JIA (10,(27)(28)(29). We can report similar findings: presence of morning stiffness, high number of swollen joints and acute phase reactants (ESR and CRP) at an early stage of disease are commonly reported as JIA or RA poor outcome risk factors.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The search of predictive factors of arthritis outcome has been the subject of many studies. Most of studies analyzed the outcome and poor prognosis in selected patients with already established JIA (10,(27)(28)(29). We can report similar findings: presence of morning stiffness, high number of swollen joints and acute phase reactants (ESR and CRP) at an early stage of disease are commonly reported as JIA or RA poor outcome risk factors.…”
Section: Discussionsupporting
confidence: 74%
“…A delay in diagnosis, treatment or follow-up may result in joint damage and bone destruction, heart, kidney disease or visual impairment. Identifying early those children who are most likely to have a severe disease course may help to target therapies to those most likely to have poor outcomes and avoid over-treatment in those most likely to experience spontaneous remission (10).…”
Section: Introductionmentioning
confidence: 99%
“…CAPS is a multicenter study in the UK with an overall aim to identify genetic and environmental predictors of short‐term and long‐term outcomes of inflammatory arthritis. Details of this study have been described elsewhere 4, 20. CAPS was approved by the North‐West Multi‐Centre Research Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…JIA is a heterogeneous disease, and during childhood and adolescence many patients experience physical and psychosocial limitations, including functional disability, pain, absence from school, and difficulties participating in other activities such as sports 2, 3. JIA not only causes problems during childhood and adolescence, but joint damage accrued during these years and ongoing exacerbations of inflammation are associated with functional and socioeconomic consequences into adulthood 2, 4, 5. With respect to the latter, a few studies have shown that despite higher rates of school absence, patients with JIA have similar or above average high school grades compared to the general population in the UK, but patients with JIA are less likely to be employed after leaving school 6, 7, 8.…”
Section: Introductionmentioning
confidence: 99%
“…Интерес представляет практически любой раздел -от определения и классификации до лечения и прогноза. Не-опровержимым остается факт: ЮИА является довольно частой патологией в группе диффуз-ных болезней соединительной ткани у детей и ведет к серьезной инвалидизации в случае неэффективного и несвоевременного лечения [1][2][3].…”
unclassified